What does it take to provide clinical interventions with temporal consistency? A qualitative study of London hyperacute stroke units. Issue 11 (7th November 2019) - Black, Georgia B; Ramsay, Angus I G; Baim-Lance, Abigail; Eng, Jeannie; Melnychuk, Mariya; Xanthopoulou, Penny; Brown, Martin M; Morris, Stephen; Rudd, Anthony G; Simister, Robert; Fulop, Naomi J
Abstract : Objectives: Seven-day working in hospitals is a current priority of international health research and policy. Previous research has shown variability in delivering evidence-based clinical interventions across different times of day and week. We aimed to identify factors influencing such variations in London hyperacute stroke units (HASUs). Design: Interview and observation study to explain patterns of variation in delivery and outcomes of care described in a quantitative partner paper (Melnychuk et al ). Setting: Eight HASUs in London. Participants: We interviewed HASU staff (n=76), including doctors, nurses, therapists and administrators. We also conducted non-participant observations of delivery of care at different times of the day and week (n=45; 102 hours). We analysed the data for thematic content relating to the ability of staff to provide evidence-based interventions consistently at different times of the day and week. Results: Staff were able to deliver 'front door' interventions consistently by taking on additional responsibilities out of hours (eg, deciding eligibility for thrombolysis); creating continuities between day and night (through, eg, governance processes and staggering rotas); building trusting relationships with, eg, Radiology and Emergency Departments and staff prioritisation of 'front door' interventions. Variations by time of day resulted from reduced staffing in HASUs and elsewhere in hospitals in the evenings and at the weekend. Variations by day of week (eg, weekend effect) resulted from lack of therapy input and difficulties repatriating patients at weekends, and associated increases in pressure on Fridays and Mondays. Conclusions: Evidence-based service standards can facilitate 7-day working in acute stroke services. Standards should ensure that the capacity and capabilities required for 'front door' interventions are available 24/7, while other services, for example, therapies are available every day of the week. The impact of standards is influenced by interdependencies between HASUs, other hospital services and social services.